Comparative Analysis of Compression Molded Products of Recycled Waste Poly(Vinyl Chloride) and Virgin Poly(Vinyl Chloride) Fill Material - Shahin Sultana; Md. Khabir Uddin Sarker; Zahidul Islam; Muhammad Saiful Islam (Journal of Engineering and Technological Sciences, 2022)
Waste poly(vinyl chloride) fill material from the cooling tower of a power plant was used for mechanical recycling. Mechanical recycling is the processing of plastic waste without changing the original chemical structure of the plastic. The waste rigid poly(vinyl chloride) fill material was cleaned, grinded and compression molded at optimized conditions of time, temperature and pressure using a compression molding machine. Virgin poly(vinyl chloride) was purchased and compression molded by the same compression molding machine. The compression molded sheets of waste poly(vinyl chloride) and virgin poly(vinyl chloride) were characterized by attenuated total reflection Fourier transform infrared analyses, tensile properties analyses, and thermal properties analyses. The results revealed that waste rigid poly(vinyl chloride) fill material is mechanically recyclable into new products such as pipes, profiles, furniture and other related products.